Experimental Study on Hydrocracking Process of Asbuton Hydrocarbon Based on the Aromatic, and Waxy Residue Based on Paraffinic, by using Pt/Pd and γ-Alumina Catalyst in a Fixed Bed Reactor - Bardi Murachman; Deendarlianto Deendarlianto; Nissaraly H.F.; Wakhid Hasyim (ASEAN Journal of Chemical Engineering, 2014)
The studies on the hydrocracking process to obtain the fuel by cracking of the carbon chain from the hydrocarbon compound both in the form of gas and liquid fuels have been carried-out massively by researchers over three decade. In the present experimental study, heavy hydrocarbon represented by asphaltic base materials (named as Extracted Asbuton) and paraffinic (waxy residue from Cepu oil refinery) were used as the object of the study; by observing the differences of the reaction mechanisms and the results that can be obtained. Here the operational conditions such as pressure, temperature, and time as well as the kinds of catalyst were considered as the main parameters. The experiments were carried-out under the similar operating condition such as temperature around 350 – 500oC, pressure around 5 up to 15 atmospheres, and evaporation time was (1 – 3) hours. As a result, it was obtained (a) the higher the temperature, pressure, and heating time, the higher hydrocracking conversion both of hydrocarbons, (b) reaction mechanism of hydrocracking by using asphalt extract as the material follows the Model 3 of the present work, in which asphalt vapor was trapped in catalyst surface, meanwhile the waxy residue followed the Model 1, (c) under the same condition, the conversion of asphalt extract was smaller than waxy residue, and (d) the conversion of asphalt extract using Pt/Pd catalyst was higher than γ-Alumina catalyst.Keywords : Asbuton, Waxy Residue, Hydrocracking, Reaction Mechanisms.